The The Impact of Reading, Covering, Remembering, Retelling on Students' Reading Comprehension - Fitriani; Abin, Rais; Suryadi, Ray; Syam, Hariadi; Reskiawan, Bimas; Sultan (Research Horizon, 2025)
The importance of reading comprehension is key for middle school children, especially in descriptive texts where narrative vivid, clear attention to the facts and sensory aspects is needed. But Indonesian eighth-grade students experienced some difficulties in reading because of a lack of vocabulary, have no reading strategy and have lower interest in reading. The purpose of study is to investigate whether the Read, Cover, Remember, Retell (RCRR) strategy effective in teaching reading comprehension of descriptive texts. A quasi-experimental approach with pre- and post-test measurements on experimental and control groups was used. Preliminary results revealed that students in both groups had mostly average reading comprehension abilities with little representation of high‐or low‐performers. The group of students that was exposed to RCRR made marked improvement - 77% in the excellent range, and one student at the level of very high. In comparison, the control group, taught in the traditional manner, gained only minimally with 55% achieving the high category and none the very high category. These findings indicate that not only does the RCRR intervention enhance comprehension, but it also leads to more students achieving advanced levels of comprehension. In short, the RCRR approach is a feasible and efficacious approach English teachers to enhance students’ comprehension and engagement with descriptive texts.